2020
DOI: 10.1186/s12939-020-01227-y
|View full text |Cite
|
Sign up to set email alerts
|

Race, socioeconomic deprivation, and hospitalization for COVID-19 in English participants of a national biobank

Abstract: Preliminary reports suggest that the Coronavirus Disease 2019 (COVID− 19) pandemic has led to disproportionate morbidity and mortality among historically disadvantaged populations. We investigate the racial and socioeconomic associations of COVID− 19 hospitalization among 418,794 participants of the UK Biobank, of whom 549 (0.13%) had been hospitalized. Both Black participants (odds ratio 3.7; 95%CI 2.5–5.3) and Asian participants (odds ratio 2.2; 95%CI 1.5–3.2) were at substantially increased risk as compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 3 publications
6
129
1
9
Order By: Relevance
“…Both U.K. studies assessed COVID-19 patients and found that Black andAsian patients were at an increased odds of hospitalization. Similar to our findings, after controlling for areas of deprivation and comorbidities, the risk for racial and ethnic minority patients persisted (21,22).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Both U.K. studies assessed COVID-19 patients and found that Black andAsian patients were at an increased odds of hospitalization. Similar to our findings, after controlling for areas of deprivation and comorbidities, the risk for racial and ethnic minority patients persisted (21,22).…”
supporting
confidence: 90%
“…median income, number of dependents, % with complete plumbing) , and employment status. ADI (20) and other indices (21)(22)(23) have been used to estimate the effects of these socioeconomic variables in aggregate on outcomes, including in COVID-19.…”
Section: Independent Variable and Confounding Variablesmentioning
confidence: 99%
“…Finally, two more RCTs have reported no association between HCQ and virological clearance [39] or prevention of disease in individuals exposed to it [40]. A number of factors could explain the difference between our results and the ones observed in these studies [32][33][34][35][36][37][38][39][40] including the following: the clinical-epidemiological design of our work; [30] the involvement of all patients admitted with COVID-19, regardless their past medical history, the time between onset of symptoms and the start of treatment, the duration of admission, and the need for oxygen; the different statistical approach; and the observation in our work of patients from private hospitals, who are likely to have a high socioeconomic status [41]. The safety of the HCQ has been questioned, as it could negatively impact the immune response to the virus, or cause abnormalities in the ECG [33,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This study focusing on the states of the Northeast region, one of the poorest regions of the country, but heterogeneous in some socioeconomic and demographic indicators, allows to verify the variations in the magnitude of the epidemic and explore the effectiveness of the social distance measures implemented in a socioeconomic and political context unfavorable. The interaction between poverty, unemployment, education level, race, and gender and has been documented as determinants of COVID-19 28,29 . People with low incomes are more exposed to infectious diseases, including SARS-CoV-2, due to the lack of access to basic sanitation and treated water, the lack of access to education and health services, the use of public transport, subject to crowding and the difficulty of self-isolating, living in precarious housing and/or with an excessive number of residents, or also because they are more often unemployed or engaged in informal jobs.…”
Section: Discussionmentioning
confidence: 99%